Variability in Limb Occlusion Pressures Across Visits and Between Limbs in Collegiate Soccer and Cross Country Athletes - Alexander Montoye; Danten McFate; Jackson Nordbeck; Ericka Bigham; Benjamin Cox; Brian Rider; Jennifer Vranish (International Universities Strength and Conditioning Association, 2024)
Our study assessed limb occlusion pressure (LOP) variability over time and between limbs. Collegiate athletes (n=42; Sample 1 = 15 soccer players, Sample 2 = 13 cross country runners, Sample 3 = 14 cross country runners) attended five visits separated by ≥48 hours (Sample 1), three visits separated by ~3 weeks each (Sample 2), or four visits separated by ~3 weeks each (Sample 3). For all samples, supine LOP was assessed in each leg (and also in each arm for Sample 3) using an automated system. Paired samples t-tests or RMANOVA were used to compare LOP between limbs and across trials, respectively. Additionally, agreement and variability across measures were assessed using intraclass correlations and mean absolute percent differences (MAPD). There were no significant differences in LOP across visits for any of the samples, with primarily moderate or good agreement (intraclass correlations r=0.29-0.88) and low variability (MAPD 4.3-9.0%). There were no significant differences in LOP between left and right limbs, with moderate to good agreement (r=0.74-0.93) and low variability (MAPD 3.2-7.2%). The demonstrated stability in LOP over time and between sides of the body suggests that LOP may not always need to be measured daily or bilaterally, adding feasibility to field-based implementation.